1993
DOI: 10.1172/jci116416
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a functional autoimmune epitope on the muscarinic acetylcholine receptor-2 in patients with idiopathic dilated cardiomyopathy.

Abstract: A peptide corresponding to the sequence 169-193 of the second extracellular loop of the human muscarinic acetylcholine receptor-2 was used as an antigen to screen sera from patients with idiopathic dilated cardiomyopathy (DCM, n = 36) and healthy blood donors (HBD, n = 40). The sera from 14 patients with DCM (38.8%) and 3 HBD (7.5%) recognized the muscarinic receptor peptide at dilutions varying from 1:20 to 1:160 in ELISA. A highly significant correlation (P = 0.006) was found between the presence of antimusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(157 citation statements)
references
References 21 publications
(26 reference statements)
3
149
0
3
Order By: Relevance
“…Certain types of antibodies may affect cardiomyocyte functions by binding membrane receptors on heart cells in DCM patients [10][11][12][13][14] and in animal models [15][16][17]. For example, agonistic anti-β 1 AR autoantibodies induce cardiomyocyte apoptosis in vitro [22] and the passive transfer of β 1 AR-specific antisera induced a DCM-like phenotype in recipient rodents in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…Certain types of antibodies may affect cardiomyocyte functions by binding membrane receptors on heart cells in DCM patients [10][11][12][13][14] and in animal models [15][16][17]. For example, agonistic anti-β 1 AR autoantibodies induce cardiomyocyte apoptosis in vitro [22] and the passive transfer of β 1 AR-specific antisera induced a DCM-like phenotype in recipient rodents in vivo [17].…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in humoral immunity play an important role in cardiac dysfunction of DCM patients. A number of autoantibodies against cardiac cell proteins have been identified in DCM: e.g., antibodies against the cardiac beta-1 adrenergic receptor, contractile proteins, mitochondrial proteins and the muscarinic acetylcholine receptor-2 [2][3][4][5][6][7]. Experimental and clinical data indicate that cardiac antibodies play an active role in the pathogenesis of DCM and may contribute to cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the first experimental observations were made by several investigators, suggesting a possible involvement of autoimmune mechanisms to cardiac autoantigens; in particular, a mouse model for myosin-induced autoimmune myocarditis was described by the Neu et al [5]. In addition, various groups in the late 80s and early 90s reported the presence of circulating anti-heart autoantibodies against myosin as well as other autoantigens in acute and chronic myocarditis or dilated cardiomyopathy, in keeping with the hypothesis of autoimmunity being involved in a subset of patients [6][7][8][9][10][11][12][13][14]. A retrospective multicenter registry from the USA coordinated by Cooper et al [15] reported the efficacy of immunosuppressive therapy in a rare but lethal form of myocarditis, e.g., giant cell myocarditis.…”
mentioning
confidence: 84%